PENGARUH PENGETAHUAN ORANG TUA DALAM MERAWAT KESEHATAN GIGI DAN MULUT TERHADAP KEBERSIHAN RONGGA MULUT ANAK TUNA GRAHITA DI SLB NEGERI KOTA KUPANG - Merniwati Sherly Eluama; Sumi Milka Asakameng; Yulwans Alu Ratu; Applonia Leu Obi; Leny Marlina A. Pinat; Mery Novaria Pay (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
This study aims to determine the effect of parental knowledge regarding dental and oral health care on the oral hygiene of children with intellectual disabilities at a special needs school in Kupang City. The research method used a quantitative approach with a cross-sectional design. Data collection was conducted through a questionnaire to measure parental knowledge and an examination of the children's oral hygiene index. Data analysis used the Spearman Rank test. The results showed a correlation coefficient (rₛ) of 0.254 with a p-value of 0.161, indicating a weak and insignificant positive relationship between parental knowledge and children's oral hygiene. Therefore, it can be concluded that parental knowledge does not significantly influence the oral hygiene of children with intellectual disabilities.